A low‐cost, wideband, dual‐circularly polarized traveling wave antenna array. Issue 3 (2nd January 2021) - Liu, Jin; Li, Jia‐Lin
Abstract: This article presents a low‐profile dual‐circularly polarized array based on the series feed and sequential rotation techniques. The basic radiation element is the microstrip based corner‐cut square patch that could achieve dual‐circularly polarized radiations. By rotating four basic elements in sequence to constitute a 2 × 2 subarray and series feeding with a phase difference of 90°, the axial ratio bandwidth can be greatly enhanced. Further, by symmetrically positioning four of such 2 × 2 subarrays coupled with out‐of‐phase feeding of the four subarrays, the beam deflection against frequency is corrected. To validate the proposed design, an 8 × 8 dual‐circularly polarized array operating at 6.0 GHz was developed and examined experimentally. Measurements and simulations confirm the design well.